2007
DOI: 10.1016/j.devcel.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical Wnt Signaling through G Protein-Linked PKCδ Activation Promotes Bone Formation

Abstract: Wnt signaling regulates a variety of developmental processes in animals. Although the beta-catenin-dependent (canonical) pathway is known to control cell fate, a similar role for noncanonical Wnt signaling has not been established in mammals. Moreover, the intracellular cascades for noncanonical Wnt signaling remain to be elucidated. Here, we delineate a pathway in which Wnt3a signals through the Galpha(q/11) subunits of G proteins to activate phosphatidylinositol signaling and PKCdelta in the murine ST2 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
288
2
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 298 publications
(305 citation statements)
references
References 71 publications
11
288
2
4
Order By: Relevance
“…In vivo studies have shown that both Lrp5/6-21 and Fzddependent pathways (32,39) influence osteoblast function and bone metabolism. However, the cellular and molecular mechanisms involved in the regulation of osteoblastic cells and bone mass by Wnt proteins remain unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo studies have shown that both Lrp5/6-21 and Fzddependent pathways (32,39) influence osteoblast function and bone metabolism. However, the cellular and molecular mechanisms involved in the regulation of osteoblastic cells and bone mass by Wnt proteins remain unclear.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in mesenchymal ST2 cells, a PKCd-dependent pathway that contributes to Wnt-induced bone formation has been described. (32) This pathway is activated by Gaq heterotrimeric proteins in response to Wnt3a, probably through frizzled receptors. A Rac1-JNK noncanonical pathway has also been described in the same mesenchymal cell line and plays an important role in limb development.…”
Section: Introductionmentioning
confidence: 99%
“…Wnt3a can also enhance ALP activity and BSP in conditional medium, enhance osteocalcin expression in ST2 cells in nondifferentiation medium, and increase mineralization in differentiation medium [86]. Wnt3a protein dose dependently induced ALP activity in ST2 cells in a serum-free medium [86].…”
Section: Wnt3amentioning
confidence: 98%
“…An initial report on the Wnt7b −/− E18.5 embryo did not show any clear skeletal phenotype [52]. However, ablation of Wnt7b from skeletal progenitors by using CreloxP technique with Dermo1-Cre results in a deficiency in embryonic bone formation, which is at least partly due to a deficit in osterix activation and subsequent osteoblast differentiation [86]. BMP2 induced Wnt1 and Wnt3a expression in C3H10T1/2 cells [87].…”
Section: Wnts-reporter Mouse Strains For Active Canonical Wnt Signalimentioning
confidence: 99%
See 1 more Smart Citation